Qualitative and quantitative study of the highly specialized lipid tissues of cetaceans using HR-MAS NMR and classical GC. - Jean-Luc Jung; Gaelle Simon; Eric Alfonsi; Didier Thoraval; Nelly Kervarec; Douraied Ben Salem; Sami Hassani; Frédéric Domergue (PLoS ONE, 2017)
Cetacean adipose tissues contain an extremely very wide variety of acyl-chains present in triacylglycerols and / or wax esters. In addition, changes in the lipid composition across organs suggest fine stratification. It therefore remains technically challenging to describe precisely the lipid organization of these tissues. In the present study, we used in parallel HR-MAS NMR (High Resolution Magic Angle Spinning Nuclear Magnetic Resonance) and GC (gas-chromatography) to characterize and quantify the lipids and fatty acyl-chains from the blubber and melon of two odontocete species. Both methods generated very similar compositions, but each presented clear advantages. While GC underestimated the amount of short branched fatty acyl-chains, which are specific to cetacean adipose tissues and most probably of primary importance for their functioning, HR-MAS NMR allowed for their exact quantification. Conversely, when HR-MAS NMR could only discriminate a few types of fatty acyl-chain families, GC unambiguously identified and quantified most of them. In addition, this technique allowed for the determination of the wax esters molecular species. Our results further suggest that the stratification of these adipose tissues relies on changes in the triacylglycerol to wax ester ratio and in the fatty acyl composition of triacylglycerols, but not on changes in the wax esters composition. Altogether, our data show that the complementarities of these two approaches result in lipid analyses of unprecedented precision, paving the way for the detailed description of the fatty acyl composition of cetacean adipose tissues and the understanding of their functioning.